STRATIGRAPHY, MICROFOSSILS, AND BIOFACIES IN THE REFERENCE SECTION OF CALLOVIAN AND UPPER JURASSIC FROM THE TYUMEN' SUPERDEEP WELL (WEST SIBERIA) - Nikitenko B.L.; Il'ina V.I.; Glinskikh L.A. (My University, 2002)
The Callovian and Upper Jurassic section in the Tyumen' superdeep well SD-6 (West Siberia) drilled with almost continuous recovery of core (about 200 m) and characterized by rich assemblages of microfossils is a unique object for development and improvement of Jurassic regional biostratigraphic schemes of West Siberia based on microfossils. This paper presents results of micropaleontological and palynological research (foraminifers, microforaminifers, ostracods, dinoflagellate cysts, acritarchs, prasinophytes as well as spores and pollen grains of terrestrial plants) and bio- and lithostratigraphic features of the uppermost Middle and Upper Jurassic part of the reference section from the Tyumen' superdeep well. The Vasyugan, Georgievka, and Bazhenov Formations are described in detail, taking into consideration their micropaleontological and palynological characteristics. The strucural features of sand productive beds of J02 and J1 groups in the Vasyugan Formation and J01 group at the base of the Georgievka Formation are discussed. Comprehensive lithostratigraphic analysis of Callovian-Upper Jurassic part of the section SD-6 and biostratigraphic data allow us to localize the boundaries of some formations, subformations, and beds in this well. The main regularities of stratigraphic and lateral distribution of Callovian and Upper Jurassic formations as well as their thickness in the Urengoi district and adjacent territories are revealed. Analysis of stratigraphic distribution of microfossil species allow a detailed zonal subdivision or reference section SD-6, with this section being the most complete Jurassic succession in northern West Siberia. The Jurassic regional-scale biostratons were revealed in Siberia according to foraminifers (f-zones), some of them being proposed for West Siberia for the first time. Also for the first time, an almost continuous sequence of dinocyst-based biostratons (dinozones) for Callovian-Middle Volgian has been established in a single section. It may be the basis for the development of Jurassic zonal scale according to dinocysts for West Siberia. Distinctive features of microbenthos communities and microphytoplankton associations reflecting biofacies have been studied. The main regularities of distribution or microbenthic communities and microphytoplankton associations depending on changes of transgressive-regressive events and paleoenvironments in the Callovian-Late Jurassic have been established.
Keywords: Jurassic; Callovian; Mesozoic::Jurassic; Mesozoic::Jurassic::Middle::Callovian; Мезозой::Юрская; Мезозой::Юрская::Средний::Келловейский